Comparison of International and Local Auditing Standards: Practical Implications - Pratama, Miko (Manunggal Halim Jaya, 2023)
This qualitative literature review explores the practical implications of auditing standard convergence, focusing on audit quality and financial reporting practices. The research aims to analyze the impact of international auditing standards, particularly the International Standards on Auditing (ISAs), on audit quality across different jurisdictions. The methodology involves a systematic search and analysis of relevant academic articles, books, reports, and scholarly sources. Data collection includes comprehensive searches of academic databases and hand-searching for relevant journals. Data analysis employs thematic analysis and quality appraisal criteria for evaluating qualitative research. The findings suggest that the adoption of ISAs is associated with improvements in audit quality due to their principles-based approach and emphasis on professional judgment and skepticism. However, the extent of improvement varies depending on the regulatory environment and institutional context. Challenges in achieving convergence arise from differences in legal systems, cultural norms, and regulatory environments across countries. Despite efforts towards convergence, discrepancies exist in research findings regarding the impact on financial reporting quality. Factors moderating this relationship include regulatory oversight, contextual differences, and institutional infrastructure. The study underscores the need for nuanced approaches to standard-setting and implementation to address these challenges effectively.